2020
DOI: 10.1093/ofid/ofaa439.1599
|View full text |Cite
|
Sign up to set email alerts
|

1417. Clinical Features and Outcomes of raoultella terrigena Infections. A Single-Center Experience from Karachi, Pakistan

Abstract: Background Raoultella terrigena (formerly Klebsiella terrigena) is an environmental gram-negative rod, occasionally causing infections in humans, especially in elderly, immunosuppressed patients. Moreover, this organism tends to be multi-drug resistant, limiting treatment options. Evidence on clinical presentation and outcomes of this infection is limited; we conducted a cross-sectional study to get a better insight into these infections. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…Raoultella terrigena infection showed high mortality (44.4%), 4 patients from 9 separately reported clinical cases with presented outcome information have died (Table 3). Similar mortality levels (44.7%) have been reported in Pakistan during 2013‐2018 years 22 . In our case, 1 of our study patient had pregnancy, eclampsia, and long‐term smoking anamnesis; in case 2, the patient had decompensation of type 1 diabetes, so we may say both patients were immunocompromised 23 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Raoultella terrigena infection showed high mortality (44.4%), 4 patients from 9 separately reported clinical cases with presented outcome information have died (Table 3). Similar mortality levels (44.7%) have been reported in Pakistan during 2013‐2018 years 22 . In our case, 1 of our study patient had pregnancy, eclampsia, and long‐term smoking anamnesis; in case 2, the patient had decompensation of type 1 diabetes, so we may say both patients were immunocompromised 23 …”
Section: Discussionsupporting
confidence: 85%
“…And 8 cases were reported in Pakistan as bacteriemia 32 . 58 cases of R. terrigena in another hospital in Pakistan were reported during 2013‐2018 years, 12 patients of which were colonized without clinical symptoms 22 . There were isolated 2 strains of R. terrigena from the gallbladders in patients with gallstones after cholecystectomy, 33 but without connection between stone formation or inflammation and isolated pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of Raoultella terrigena infections is known to be a very rare, however some studies have reported the isolation of R. terrigena from several clinical sites, such as urinary tract (Wang, et al, 2016;Mal, et al, 2019;Ahmed, et al, 2020;Lekhniuk, et al, 2021). Until the date of this study, just about 363 cases of R. terrigena infections have been published in the world, while according to our knowledge there is no reported cases either in Libya or Arabic countries (Lekhniuk, et al, 2021).…”
Section: Resultsmentioning
confidence: 73%
“…The first documented case of R. terrigena as a human pathogen was confirmed in 2007 in a patient with a post-liver transplant and endocarditis (Goegele et al, 2007). This bacterium has been isolated from other different clinical sites such as subungual abscess, bronchial secretion, blood and urine (Wang, et al, 2016;Mal, et al, 2019;Ahmed, et al,. 2020;Lekhniuk, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation